2015
DOI: 10.1016/j.apjtm.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serum Dickkopf-1 in gastric cancer patients

Abstract: The expression of serum DKK-1 protein in gastric cancer patients is increased. Level of serum DKK-1 is related to TNM staging, microvascular invasion, differentiation degree and infiltration depth. DKK-1 detection can be used as a reference index in monitoring gastric cancer progress and biological behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…55 But what is the expression of Dkk1 in patients with gastric cancer and its clinical significance? Zhuang et al 56 detected the expression of serum Dkk1 protein in 90 cases of gastric cancer, 50 cases of gastric benign disease and 40 healthy persons by ELISA, and the dynamic changes of serum Dkk1 protein in gastric cancer patients undergoing radical operation for 1 month. It was found that the expression of serum Dkk1 protein in the gastric cancer group was significantly higher than that in the gastric benign group and the healthy control group.…”
Section: Expression Of Dkk1 In Gastric Cancermentioning
confidence: 99%
“…55 But what is the expression of Dkk1 in patients with gastric cancer and its clinical significance? Zhuang et al 56 detected the expression of serum Dkk1 protein in 90 cases of gastric cancer, 50 cases of gastric benign disease and 40 healthy persons by ELISA, and the dynamic changes of serum Dkk1 protein in gastric cancer patients undergoing radical operation for 1 month. It was found that the expression of serum Dkk1 protein in the gastric cancer group was significantly higher than that in the gastric benign group and the healthy control group.…”
Section: Expression Of Dkk1 In Gastric Cancermentioning
confidence: 99%
“…The protein encoded by Dickkopf-1 (DKK1) is involved in inhibition of the Wnt signaling pathway and maintains the immunosuppressive effects of the tumor microenvironment. Notably, DKK1 has been reported to be highly expressed in various tumor types, including gastric cancer (49). Leap Therapeutics announced that its anti-DKK1 antibody, DKN-01, in combination with Merck's anti-PD-1 antibody, Keytruda ® (pembrolizumab), demonstrated improved outcomes in patients with advanced gastroesophageal junction and gastric cancer when the tumors expressed high levels of DKK1 (DKK1-high).…”
Section: Icis and Other Molecular Targeted Therapiesmentioning
confidence: 99%
“…High levels of DKK1 in vitro are associated with a more invasive phenotype, and in patients, correlated with poorer OS. 33 DKN-01 is a monoclonal antibody to this protein which is under study in combination with paclitaxel in progressive DKK1 + (by IHC) metastatic or unresectable esophageal cancer and gastroesophageal junction adenocarcinoma. 34 In this study >90% of screened patients had DKK1 + tumors.…”
Section: Treatment Approachesmentioning
confidence: 99%